2015
DOI: 10.1253/circj.cj-14-1372
|View full text |Cite
|
Sign up to set email alerts
|

Direct Reprogramming of Fibroblasts into Cardiomyocytes for Cardiac Regenerative Medicine

Abstract: Cardiac fibroblasts play critical roles in maintaining normal cardiac function and in cardiac remodeling during pathological conditions such as myocardial infarction (MI). Adult cardiomyocytes (CMs) have little to no regenerative capacity; damaged CMs in the heart after MI are replaced by cardiac fibroblasts that become activated and transform into myofibroblasts, which preserves the structural integrity. Unfortunately, this process typically causes fibrosis and reduces cardiac function. Directly reprogramming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 81 publications
0
33
0
3
Order By: Relevance
“…Indeed, because of the injury-induced fibroblast-myofibroblast transdifferentiation process, these cells might represent a population of plastic cells that can be more easily reprogrammed further into another cell type. The direct reprogramming of fibroblasts/myofibroblasts into induced cardiomyocyte-like cells (iCMs) with the help of cardiac transcription factor overexpression was first reported by Ieda et al in 2010 (Ieda et al 2010), and since then, several groups have reported successful cardiac reprogramming with various strategies, both in vitro (Table 2) and in vivo (Table 3; for reviews, see, for example, Srivastava and Berry 2013; Fu and Srivastava 2015; Sahara et al 2015; Srivastava and Yu 2015). …”
Section: Fibroblast Reprogramming - Harnessing Fibrosis To Induce Regmentioning
confidence: 99%
“…Indeed, because of the injury-induced fibroblast-myofibroblast transdifferentiation process, these cells might represent a population of plastic cells that can be more easily reprogrammed further into another cell type. The direct reprogramming of fibroblasts/myofibroblasts into induced cardiomyocyte-like cells (iCMs) with the help of cardiac transcription factor overexpression was first reported by Ieda et al in 2010 (Ieda et al 2010), and since then, several groups have reported successful cardiac reprogramming with various strategies, both in vitro (Table 2) and in vivo (Table 3; for reviews, see, for example, Srivastava and Berry 2013; Fu and Srivastava 2015; Sahara et al 2015; Srivastava and Yu 2015). …”
Section: Fibroblast Reprogramming - Harnessing Fibrosis To Induce Regmentioning
confidence: 99%
“…There are two approaches to achieving cell fate conversion, lineage-specific transcription factors and Yamanaka factors (Sox2, Klf4, Oct4, and c-Myc) [102104]. Cardiomyocytes could be generated through overexpressing cardiac-specific transcription factor (Gata4, Mef2c, and Tbx5 or cardiac microRNAs) [102, 105125] or Yamanaka factors in fibroblast cells [111, 123] (Supplementary Table 2). …”
Section: Cell Fate Conversion Via Somatic Reprogramming In Cardiac Cellsmentioning
confidence: 99%
“…Этот процесс включает в себя высокоре-гулируемую деятельность по синтезу и деградации кол-лагена. Синтезу коллагена способствуют профиброген-ные факторы роста, в том числе трансформирующий фактор роста-β1 (TGF-β1), а деградация коллагена осу-ществляется членами семейства матриксных металло-протеиназ (ММР) [7][8][9].…”
Section: клеточная регуляция фиброзаunclassified
“…В ответ на эти стимулы эта сложная сеть регулирует продукцию внекле-точного матрикса и гипертрофию кардиомиоцитов и в меньшей степени -пролиферацию кардиомиоцитов, кроме того, она вызывает активацию фиброзных и вос-палительных процессов. Следует отметить, что в зависи-мости от окружающей микросреды формируются различ-ные фенотипы сердечных фибробластов [5,6,9].…”
Section: клеточная регуляция фиброзаunclassified
See 1 more Smart Citation